Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1021/bi801451f
|View full text |Cite
|
Sign up to set email alerts
|

The Adiponectin Receptors AdipoR1 and AdipoR2 Activate ERK1/2 through a Src/Ras-Dependent Pathway and Stimulate Cell Growth

Abstract: Adiponectin is an adipocyte-derived cytokine that has attracted much attention because of its insulin-sensitizing effects in liver and skeletal muscle. Two adiponectin receptors, AdipoR1 and AdipoR2, have been cloned, but relatively little is known about their intracellular signaling mechanisms. We found that full-length adiponectin rapidly and robustly activates the ERK1/2 mitogen-activated protein kinase pathway in primary vascular smooth muscle, vascular endothelial cells, and hepatocytes. In a HEK293 cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 42 publications
4
87
1
3
Order By: Relevance
“…Furthermore, these investigators showed a similar response occurred in endothelial and HEK293 cells and that adiponectin stimulated the proliferation of HEK293 cells (Lee et al 2008).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Furthermore, these investigators showed a similar response occurred in endothelial and HEK293 cells and that adiponectin stimulated the proliferation of HEK293 cells (Lee et al 2008).…”
Section: Discussionmentioning
confidence: 74%
“…In contrast to these observations, however, Lee et al (2008) reported that treatment of SMCs with adiponectin resulted in ERK1/2 activation. Furthermore, these investigators showed a similar response occurred in endothelial and HEK293 cells and that adiponectin stimulated the proliferation of HEK293 cells (Lee et al 2008).…”
Section: Discussionmentioning
confidence: 79%
“…45 Both contain seven transmembrane domains but are structurally and functionally distinct from G-protein-coupled receptors. Unlike G-proteincoupled receptors, the amino (N)-termini of both receptors are intracellular and the C-terminal end is extracellular and binds adiponectin.…”
Section: Adiponectin Mediates Crosstalk Between Adipose Kidney and mentioning
confidence: 99%
“…In endothelial cells, adiponectin can activate AMPactivated protein kinase through APPL1 to provide a survival signal (15). Alternatively, adiponectin activates the ERK pathway through APPL-dependant Ras activation (16). Nevertheless, APPL mediates the adiponectin-induced phosphorylation of endothelial nitric-oxide synthase, and the subsequent production of nitric oxide that triggers endothelium-dependent vasodilation (17).…”
mentioning
confidence: 99%